Interrelationship among capital structure, corporate governance measures and firm value: Panel study from Pakistan - Awais Javeed; Masood ul Hassan; Muhammad Azeem (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
The aim of the study is to test most discussed relationship between capital structure and firm value. This research also investigated the impact of corporate governance measures on firm value and impact of capital structure on corporate governance measures. The study used the 775 firm year observations of 155 non-financial companies listed at Karachi Stock Exchange for financial years containing 2008 to 2012. Keeping in view the nature of data (balanced panel), fixed effects regression method is employed to estimate the formulated relationships. For first relationship of interest (impact of capital structure on firm value) the study found significant positive impact, but in case of corporate governance, only board independence and ownership concentration measures are found affecting firm value significant with positive sign. For third relationship i.e., impact of leverage on governance measures, this study found no significant affects.
Keywords: 330; capital structure; corporate governance measures; firm value; non-financial firms; Karachi stock exchange